THE DIODE LASER USAGE IN THE TREATMENT OF DENTAL CARIES IN CHILDREN WITH NEUROPSYCHIATRIC DISORDERS - O. V. Gulenko; V. V. Volobuev (Кубанский научный медицинский вестник, 2016)
There is a high level of intensity and prevalence of dental hard tissue diseases in children with neuropsychiatric disorders. Taking into account the difficulty and specificity in the treatment of this category of children, in particular, the impossibility of full cavity necrectomy, the problem of caries complications after treatment is relevant. For high quality tooth decontamination before filling, we suggested to use the bactericidal properties of the laser beam (810 nm), because the creation of «sterile» cavity is one of the most important components of a favorable prognosis of treatment. The proposed method of treatment is effective due to the full bactericidal effect, reduces the risk of complications and can serve as an alternative to the previously proposed methods for the treatment of acute decompensated form of caries.